Generating Thinking skills of students Applicants in the Department of Mathematics/ College Of Basic Education (Journal of the College of Basic Education, 2019)
The goal of research is to identify the skills of thinking generation Students in the Department of Mathematics / College of Basic Education.The research sample consisted of (66) students from the fourth stage. A total of (28) paragraphs (17), objective paragraphs (11), and (4) paragraphs of each of the seven generating Thinking skills have been tested,The apparent honesty and validity of the construction were tested for the test, and the Alpha Krobach equation was used to calculate stability (0.82) Using the appropriate statistical methods, it was found that the performance of students applicants to the test of generting thinking was higher than the mean, but the differences were not statistically significantIn the light of these results, a set of recommendations and proposals have been issued, including the need to review university education based on the skills of generating thinking, and the need to carry out research complementary to the current research.